Patriarchy and Gender Categories in Pakhtunwali: Family, Socialization and the Women Agency in Peshawar Valley - Abu Hurara, (Dialogue Social Science Review (DSSR), 2025)
This article deals with the interaction and relationship of gender in Pakhtunwali and seeks to explore the concepts of Pakhtun codes of life and behavior in terms of family, segregation and the women agency; how Pakhtunwali represents men and women through socialization and its pattern, how and why Pakhtunwali identifies gender categories in the form(s) of patriarchy. It explores the position of Pakhtun woman, her nature, and practice both within the public and private sphere of society, particularly in Peshawar valley. It understands the question that how, and why did Pakhtuns women subordination came into existence if they have a strong bond of emotions in Gham-Khadi? And how female-female alliances are performed as an agency and how does patriarchy use that performance as its strategy through females themselves?